Markers of bone metabolism in patients with systemic scleroderma - Yu. Yu. Ivanova; O. V. Bugrova; K. A. Nagornova; R. I. Sayfutdinov (Современная ревматология, 2020)
The mechanism of development of osteoporosis (OP) in systemic scleroderma (SSc), despite ongoing studies on this subject, remains not completely clear.Objective. To assess the state of bone mineral density (BMD) in patients with systemic scleroderma (SSc) and to determine the level of bone metabolism markers (osteocalcin, b-CrossLaps) in blood serum.Methodology. We examined 65 patients with SSc: 6 (9%) men and 59 (91%) women, with an average age of 51 [39;61] years and 35 relatively healthy individuals comparable in basic anthropometric parameters with patients of the main group. The main population risk factors for osteoporosis were assessed. Bone mineral density (BMD) was assessed using dual energy X-ray absorptiometry (DXA). The level of vitamin D, osteocalcin (OC), and b-CrossLaps in blood serum was determined by enzyme immunoassay.Results. A decrease in BMD was significantly more often observed in patients with SSc - 46 (71%) than in controls - 11 (31%). Significant risk factors for OP in SSc were the presence of menopause that occurred at an early age, low physical activity, hypovitaminosis D, probably high activity and duration of the disease. In patients with SSc, there was a significant decrease in the level of OK compared with the control; in the presence of a decrease in the BMD, the content of OK was significantly lower than with a normal BMD. Mean values ​​of b-CrossLaps in SSc were comparable with the control; in patients with OP, the parameter was lower than in those with normal BMD.Conclusion. OP develops significantly more often in SSc compared to the control. Risk factors for OP are early menopause, low physical activity, duration and activity of SSc. The predominance of bone formation disorders to a greater extent than bone resorption as a mechanism for the development of secondary OP was noted.